KUALITAS PELAYANAN PUBLIK DALAM PENGURUSAN DOKUMEN PERTANAHAN DI KANTOR KECAMATAN SIGI BIROMARU KABUPATEN SIGI - Rini, Rahma (Katalogis, 2016)
This study aimed to analyze the quality of public services in land document handling at the District Office of Sigi Biromaru Sigi Regency. Informants in this study amounted to 9 people, consisting of four employees and five people. Technique used in determining the informants was purposive selection, or choosing informant deliberately. Data collection techniques in this study were observations, interviews, and documentations. The result shows that the quality of public services in land document handling at the District Office of Sigi Biromaru had not been implemented optimally. This was evidenced by three of the five indicators used as benchmarks in this study, namely a. Reliability whose parameter was keeping time appointments: the land document completion was not in accordance with the time appointed; b. Tangible (Physical Evidence) whose three aspects, namely land document handling supporting facilities, waiting room situation, and tidiness of Sigi Biromaru District’s apparatus: the three aspects had not been implemented in accordance with the expectations; and c. Assurance whose knowledge aspect: from the two employees, there had been no one who ever follow any training with regard to land document handling. Only two indicators were fulfilled properly, namely d. Responsiveness given by the District Government’s officials to the people who were experiencing difficulties in land document handling had been good, and e. Empathy which indicated that the District Government’s officials had treated people fairly.